Civil Liberties vs Counter-Terror Financing Laws: A Pakistani Legal Analysis (Al-Qamar, 2025)
Over the past decades, counter-terror financing (CTF) legislation has become one of the most obtrusive tools of state authority, allowing governments to control, limit and incapacitate financial operations in the guise of national security. In Pakistan, the growth of CTF measures, namely, the Anti-Money Laundering Act 2010 (AMLA), the Anti-Terrorism Act 1997 (ATA), the targeted financial sanctions, and the regulatory AML/CFT frameworks, has substantially changed the dynamics between the security and civil liberties. These statutes bestow powers in the state and financial institutions to freeze assets, track transactions, proscribe organizations and limit economic involvement, frequently at a pre-trial or even pre-investigation phase.The research article is a comprehensive doctrinal and constitutional examination of the counter-terror financing regime in Pakistan with reference to its implications on fundamental rights as a right to fair trial and due process as found in Article 10A of the Constitution of Pakistan. It contends that even though the CTF framework in Pakistan has become internationally compliant particularly in regard to FATF monitoring, it is constitutionally frail as it is dominated by poor procedural protection, insufficient judicial checks and balances as well as acceptance of preventive financial coercion. The article concludes that counter-terror financing and civil liberties do not necessarily go at cross purposes; nonetheless, a balance between the two can be achieved by reinstating constitutional values of legality, proportionality, and accountability in the Pakistani AML/CFT enforcement framework.
Keywords: Counter-terror financing; civil liberties; Anti-Money Laundering Act 2010; Anti-Terrorism Act 1997; FATF compliance; Article 10A; due process; preventive justice; Pakistan constitutional law